Potensi Pemanfaatan Limbah Kotoran Ternak Sapi Sebagai Pupuk Kompos Ramah Lingkungan - Muzammil, Muhammad Hasan; ., Sudarti; ., Yushardi (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
The utilization of cow dung waste as compost has significant positive impacts on the agricultural sector and the environment. This article describes the production process of compost fertilizer and analyzes its impact on soil fertility, crop productivity, and reduction of environmental pollution. Compost fertilizer not only improves soil structure and provides balanced nutrition for plants, but also reduces the amount of waste discharged into the environment. The discussion will cover the technical aspects of compost production, its impact on soil quality, and the need for further research to support sustainable agriculture. The utilization of cow dung waste as compost provides important benefits that can improve the understanding and practice of sustainable agriculture.